A polymerase chain reaction enzyme immunoassay for diagnosing infection caused by Aspergillus fumigatus. - Golbang, N (1999)
AIM: To develop a polymerase chain reaction enzyme immunoassay (PCR-EIA) to measure levels of circulating aspergillus DNA in invasive aspergillosis caused by Aspergillus fumigatus. METHODS: The PCR reaction was based on primers from the 18s rRNA gene. Binding of the product to a streptavidin coated microtitration plate was mediated by a biotinylated capture probe. The product was digoxigenylated during PCR and this was the tag to which antibody was bound in the subsequent EIA. RESULTS: The optical density (OD) endpoint was < 0.1 in 10 sera from neutropenic patients with no evidence of invasive aspergillosis, and in 10 sera from nonneutropenic patients with bacterial pneumonia (group 1). The OD from five of 12 patients with allergic bronchopulmonary aspergillosis (ABPA) (group 2), three with an aspergilloma (group 3), and five with possible invasive aspergillosis (group 4) was > or = 0.1. In 63 sera from 33 cases of proven invasive aspergillosis (group 5) an OD > or = 0.1 was achieved in 48 sera from 30 patients. The maximum OD was 0.510. The level fell in survivors and gradually rose in fatal cases. CONCLUSIONS: This assay validated the concept of diagnosing invasive aspergillosis by measuring levels of circulating fungal DNA in serum.